Hydrodynamic characterisation of high and low molecular weight glycans - Lithgo, Ryan M. (2018)
Glycans are a diverse group of biological macromolecules that are made up of polysaccharides and glycoconjugates, such as glycoproteins and glycopeptides. The different types of glycans results in a multitude of structures, properties and functions. This investigation looks at the different hydrodynamic properties of several glycans including viscosity, sedimentation coefficient and molecular weight. These parameters are determined using techniques such as viscometry and Analytical Ultracentrifugation (AUC). A foundation on the principles of the techniques involved in hydrodynamic characterisation was provided through the use of ovalbumin, a glycoprotein that has been extensively studied. The study gave a basic understanding in Analytical Ultracentrifugation. Using the knowledge obtained from that investigation a study into possible reasons why the ‘last-resort’ glycopeptide antibiotic, vancomycin, is not commonly administered orally due to poor absorption within the gut. The study examined at the interactions of vancomycin with common macromolecules found with the gastro-intestinal tract, such as mucin, and trying to explain reasons how these interactions could inhibit the absorption of vancomycin. Finally investigations into two different species derived β-glucans, that have been shown to have medically benefiting properties, were characterised. The used of different hydrodynamic techniques yielded results that generally supported the accepted hydrodynamic properties of β-glucans, however there were results that challenged these understandings as well.